2016
DOI: 10.1016/j.canlet.2016.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor (PR) polyproline domain (PPD) mediates inhibition of epidermal growth factor receptor (EGFR) signaling in non-small cell lung cancer cells

Abstract: Recent evidence has suggested a possible role for progesterone receptor (PR) in the progression of non-small cell lung cancer (NSCLC). However, little is known concerning roles of PR in NSCLC. PR contains a polyproline domain (PPD), which directly binds to the SH3 domain of signaling molecules. Because PPD-SH3 interactions are essential for EGFR signaling, we hypothesized that the presence of PR-PPD interfered with EGFR-mediated signaling and cell proliferation. We examined the role of PR-PPD in cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 53 publications
1
19
1
Order By: Relevance
“…However, a recent study also indicates that extranuclear PR actions can interfere or block growth-promoting signaling pathways. Expression of PR-B in NSCLC cells [77], independent of progestins, was shown to inhibit cell proliferation via PR-PPD mediated inhibition of the EGFR-mediated MAPK signaling pathway [77].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study also indicates that extranuclear PR actions can interfere or block growth-promoting signaling pathways. Expression of PR-B in NSCLC cells [77], independent of progestins, was shown to inhibit cell proliferation via PR-PPD mediated inhibition of the EGFR-mediated MAPK signaling pathway [77].…”
Section: Introductionmentioning
confidence: 99%
“…To identify PRA and PRB interacting partners, we applied a Tet-on lentiviral transduction technique to transduce PRA or PRB into T47DC42 (ER -, PR-) breast cancer cells, as previously described 20 , 28 . To check the expression of PRA and PRB, T47DC42-PRA and T47DC42-PRB 200,000 cells were plated in phenol red-free DMEM (Dulbecco’s modified eagle medium), 5% DCC-FBS (Dextran-coated charcoal-stripped FBS; Gibco/Life Technologies) and 1% penicillin/streptomycin (PenStrep) in a 6-well plate and incubated overnight.…”
Section: Methodsmentioning
confidence: 99%
“…48 Studies have shown the importance of PR through PPD interaction in EGFR-mediated NSCLC proliferation and signal transduction. 49 Therefore, endocrine regulation is predicted to be helpful in the treatment of lung cancer. PGHS2 can be induced to produce prostaglandins, which mediate responses to physiological stress such as infection and inflammation.…”
Section: Analysis Of Yqsjf-lung Neoplasms-gene Data Set and Its Ppi Networkmentioning
confidence: 99%